A novel emotion profiling based on Cmac-based computational models of affects - Yaacob, Hamwira Sakti; Abdul Rahman, Abdul Wahab; Dzulkifli, Mariam Adawiah; Kamaruddin, Norhaslinda (IIUM Press, International Islamic University Malaysia, 2017)
Mental health has become a global concern because of the increasing number of cases related to mental illnesses over the years. This includes depression, anxiety disorders, personality disorders and other psychiatric disorders which place heavy burdens on the global societal well-being and economical growths. In general, mental health is always associated with the states of emotion which can be measured based on several affective dimensions. Emotion plays an important role in various aspects of human daily lives. It can be captured and measured from various responses, such as self-assessment, automatic nervous systems (ANS) responses, facial expressions, voice, speech text, body language and posture and the brain states. Although emotion can be easily acted, it is hardly detected through other forms of emotional expressions. However, such fraudulent is more apparent through the neurophysiology manifestations.